Dynamic programming based operation of reservoirs : applicability and limits / K.D.W. Nandalal, Janos J. Bogardi. - 388378 Nandalal, K. D. W.; Bogardi, Janos (New York : Cambridge Univ Pr., 2007)
PSZJBL